PEMENUHAN NUTRISI PADA IBU MENYUSUI DI RS CIPUTRA HOSPITAL 2022 - Ratnasari, Febi; Fajarwati, Wahyu; Damayanti , Shella; Reskawati, Shindy Ainun; Pratiwi , Sindi; Paujiah, Siti Ika; Mudattiiles, Siti Min; Saropah, Siti; Srimulyati, Siti (Nusantara Hasana Journal, 2022)
Breastfeeding is a natural way to provide food and drink in early life for babies. During breastfeeding, the nutritional needs of the mother need to be considered because the mother must not only meet her own needs but also produce breast milk (ASI) for her baby. Meeting the nutritional needs of breastfeeding mothers is a balanced menu arrangement consisting of energy, protein, fat, vitamins, and minerals. Smooth Breast Milk (ASI) is a lot of breast milk and seeps out through the nipples, before being fed the breasts feel tense. Satisfying breast milk according to age will increase the baby's weight and make the baby sleep peacefully. This health education is held to provide knowledge about good nutrition for breastfeeding mothers to facilitate breastfeeding and growth and development of babies. The method used in this counseling is a lecture by delivering material about the fulfillment of nutrition in breastfeeding mothers. Respondents have understood what has been conveyed and respondents are able to repeat what the communicator said. Fulfillment of good nutrition for breastfeeding mothers can facilitate breastfeeding.